Multi-omics approaches in long Covid investigation: immunoassay-based diagnosis, lipidomic and metabolomic analysis - Silva, Mônica Duarte da (2025)
Long COVID is a multifactorial and long-lasting condition that affects a significant proportion of individuals following SARS-CoV-2 infection, characterized by persistent symptoms such as fatigue, cognitive dysfunction, and cardiovascular alterations. It is estimated that 30% to 60% of infected individuals experience symptoms lasting longer than 12 weeks. Despite advances in the understanding of acute infection, the pathophysiological mechanisms underlying Long COVID remain poorly understood, with hypotheses involving viral persistence, immune dysregulation, and metabolic disturbances. To investigate these alterations, this thesis employed omics technologies, with a focus on metabolomic and lipidomic approaches using mass spectrometry. We developed a paper-based immunoassay for the sensitive detection of the SARS- CoV-2 nucleocapsid (N) protein, integrating an innovative amplification strategy using dendrimers and a cleavable ionic probe coupled to mass spectrometry. This method achieved a limit of detection (LOD) of 2.4 pM and demonstrated stability after 30 days of storage at room temperature, showing promise for both point-of- care (POC) and direct-to-consumer (DTC) applications. Additionally, we conducted targeted lipidomic analysis using Multiple Reaction Monitoring (MRM) on plasma samples from Long COVID patients, revealing significant alterations in the levels of lysophosphatidylcholine (LPC), phosphatidylcholine (PC), cholesteryl esters (CE), and fatty acids (FA), with emphasis on mitochondrial dysfunction and dysregulation of glycerophospholipid and sphingolipid metabolism. Several lipid species demonstrated strong discriminatory power (AUC>0.89), indicating their potential as biomarkers for the condition. Finally, we explored the novel application of pinhole paper spray mass spectrometry using embossed, hydrophobic paper substrates, enabling rapid and direct analysis of human plasma without prior sample preparation. Untargeted metabolomic analysis revealed distinct metabolic profiles between groups, highlighting alterations in lipid metabolism, mitochondrial function, and inflammatory pathways. These findings underscore the potential of paper-based approaches integrated with mass spectrometry as promising tools for clinical screening, biomarker discovery, and elucidation of the molecular mechanisms underlying Long COVID, with significant implications for the development of personalized diagnostic and therapeutic strategies.